2006
DOI: 10.1021/jp063074r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Metal−Organic Framework Compound Cu3(benzene 1,3,5-tricarboxylate)2 by Means of 129Xe Nuclear Magnetic and Electron Paramagnetic Resonance Spectroscopy

Abstract: 129Xe NMR measurements of adsorbed xenon are shown for the first time to be a suitable tool to characterize the porosity and the properties of the metal-organic framework Cu3(BTC)2(H2O)3 (BTC = benzene 1,3,5-tricarboxylate). The NMR experiments are performed at room temperature and over a wide range of xenon pressure and on two different synthesized Cu3(BTC)2 samples. 129Xe NMR results reveal that in dependence on the kind of the synthesis pathway either one or two signals are observed which can be attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…The smaller pockets have diameters of 0.50 nm, whereas the larger cavities have diameters of 1.06 and 1.24 nm. The window into these small pockets is $0.46 nm, and previous experimental work using 129 Xe NMR spectroscopy 30 has demonstrated that these sites are accessible to xenon. Based on the size of krypton and xenon, whose Lennard-Jones diameters are 0.3636 and 0.4100 nm, respectively, these pockets should be accessible as adsorption sites.…”
Section: Methodsmentioning
confidence: 91%
“…The smaller pockets have diameters of 0.50 nm, whereas the larger cavities have diameters of 1.06 and 1.24 nm. The window into these small pockets is $0.46 nm, and previous experimental work using 129 Xe NMR spectroscopy 30 has demonstrated that these sites are accessible to xenon. Based on the size of krypton and xenon, whose Lennard-Jones diameters are 0.3636 and 0.4100 nm, respectively, these pockets should be accessible as adsorption sites.…”
Section: Methodsmentioning
confidence: 91%
“…Such parameters are the chemical shift, the line width, the chemical shift anisotropy, and the longitudinal relaxation time T 1 . A first application of 129 Xe NMR spectroscopy to MOFs has been reported in 2006 [179]. Subsequently, other authors made use of the favorable properties of 129 Xe NMR in order to study MOFs [23,180,181,182,183].…”
Section: Solid-state Nmr Spectroscopic Studies Of Host–guest Intermentioning
confidence: 99%
“…1). 1,2,8,14,15 The next gas adsorption sites that become occupied are the four windows that lead into this pocket (Fig. Many previous works on HKUST-1 have shown that for Kr and Xe, the most favorable site is at the center of the small pockets in the structure (Fig.…”
mentioning
confidence: 97%